Neurosurgery specialty training in the UK: What you need to know to be shortlisted for an interview. (September 2020) - Solomou, Giorgos; Murphy, Suzanne; Bandyopadhyay, Soham; Horsfall, Hugo Layard; Mohan, Midhun; Chari, Aswin; Sinha, Saurabh; Mendoza, Nigel
Abstract: Neurosurgery is one of the most competitive specialties in the UK. In 2019, securing an ST1 post in neurosurgery corresponds to competition ration of 6.54 whereas a CST1 post 2.93. Further, at ST3 level, neurosurgery is the most competitive. In addition, the number of neurosurgical training posts are likely to be reduced in the coming years. A number of very specific shortlisting criteria, aiming to filter and select the best candidates for interview exist. In the context of the high competition ratios and the specific shortlisting criteria, developing an interest in the neurosciences early on will allow individuals more time to meet the necessary standards for neurosurgery. Here, we aim to outline the shortlisting criteria and offer advice on how to achieve maximum scores, increasing the likelihood to be shortlisted for an interview. Highlights: Neurosurgery is one of the most competitive specialities in the UK. At ST3 level neurosurgery is the most competitive surgical speciality in the UK. Leadership and management skills are desirable skills in the NHS.